Peer Observations of Observation Units - Stormoen, Camilla (UiT Norges arktiske universitet, 2018)
The Arctic Tundra in the far northern hemisphere is one of ecosystems that are most affected by the climate changes in the world today. Five Fram Center institutions developed a long-term research project called Climate-ecological Observatory for Arctic Tundra (COAT). Their goal is to create robust observation systems which enable documentation and understanding of climate change impacts on the Arctic tundra ecosystems. This thesis describes a prototype of a Wireless Sensor Network (WSN) system where nodes in the network creates clusters of Observation Units (OUs) to accumulate data. The purpose is to fetch and accumulate data observed by OUs for further use and to provide for a more flexible and powerful sensor in the coat monitoring of the Arctic Tundra. We describe a system where nodes discover each other through a range limited broadcast. Together they form clusters. Each cluster elect a Cluster Head (CH) which is responsible for sending out a request for gather and accumulate data from the other nodes in the cluster. The role as CH is rotating among the nodes to conserve battery. Results show that the system have a steady memory usage between 60% and 76% and CPU usage around 75% during execution. Experiments also show that the CH received fewer packets of data compared to sent packets from OUs in the cluster which indicates that the OUs in the system accumulates data when intended. The proposed prototype of the system proved capable of electing CHs that gathers and accumulates data efficiently. As a prototype, it still has room for improvements such as the availability of nodes in the system, CH-elections and multiple CHs in each cluster. A future system could further investigate the benefits of having multiple CHs and how to gather and accumulate data more efficiently. There is still a need for conducting further work for a real-life environment in the Arctic Tundra.